2018
DOI: 10.3762/bjnano.9.68
|View full text |Cite
|
Sign up to set email alerts
|

A review of carbon-based and non-carbon-based catalyst supports for the selective catalytic reduction of nitric oxide

Abstract: Various types of carbon-based and non-carbon-based catalyst supports for nitric oxide (NO) removal through selective catalytic reduction (SCR) with ammonia are examined in this review. A number of carbon-based materials, such as carbon nanotubes (CNTs), activated carbon (AC), and graphene (GR) and non-carbon-based materials, such as Zeolite Socony Mobil–5 (ZSM-5), TiO2, and Al2O3 supported materials, were identified as the most up-to-date and recently used catalysts for the removal of NO gas. The main focus of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 156 publications
(195 reference statements)
0
11
0
Order By: Relevance
“…However, few studies have examined AC-supported transition metal oxides during HC-SCR reactions [7]. Because MnOx has exhibited promising low-temperature HC-SCR reactivity and AC supports have excellent stability and low rates of ammonium salts accumulation [25,50,57,58], this study aimed to investigate the low-temperature catalytic performance of manganese/AC catalysts while using C 2 H 4 as a reductant. Besides the reaction testing, deactivation mechanisms were also examined using SEM/EDS, X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscope and selected area electron diffraction (TEM-SAED), and X-ray photoelectron spectrometer (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have examined AC-supported transition metal oxides during HC-SCR reactions [7]. Because MnOx has exhibited promising low-temperature HC-SCR reactivity and AC supports have excellent stability and low rates of ammonium salts accumulation [25,50,57,58], this study aimed to investigate the low-temperature catalytic performance of manganese/AC catalysts while using C 2 H 4 as a reductant. Besides the reaction testing, deactivation mechanisms were also examined using SEM/EDS, X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscope and selected area electron diffraction (TEM-SAED), and X-ray photoelectron spectrometer (XPS).…”
Section: Introductionmentioning
confidence: 99%
“…Type of catalyst supports play important roles in both activity and mechanical strength of catalysts, since they influence not only the morphology and dispersion of catalyst particles but also the activity of catalysts. [44][45][46] Many studies of graphene oxide (GO) as catalyst support, which is prepared by chemical oxidation of natural graphite followed by exfoliation, seems to be more fascinating due to its abundant functional groups, including COOH and OH, as well as its unique 2D structure. [47][48][49] Zhang et al reported that GO can probably provide efficient nucleation sites and enhance the MOFs growth, while offered higher dispersive forces of MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, carbon materials such as graphene, graphene oxide, carbon quantum dots, graphene quantum dots, carbon nanotubes, and graphitic carbon nitride have emerged as a new class of materials for energy conversion and storage devices such as supercapacitors [27,28], batteries [29,30], catalysts [31,32], and photovoltaic devices [33,34]. Because of their tunable optical and electrical properties, carbon materials have been thoroughly investigated as either hole transport layers or electron transport layers in solar cells [35].…”
Section: Introductionmentioning
confidence: 99%